Mathesis Universalis, Computability and Proof - Centrone, Stefania; Negri, Sara; Sarikaya, Deniz; Schuster, Peter M. (Synthese Library, Studies in Epistemology, Logic, Methodology, and Philosophy of Science, 2019)
X, 374 p. 38 illus.